Pelatihan Pembuatan Sabun Cair Pencuci Piring Bagi Mahasiswa Universitas Aufa Royhan Di Kota Padangsidimpuan - Ayus Diningsih; Yulia Vera (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Soap is a material used for washing clothes, furniture, bodies, etc which is made from a mixture of alkalis (sodium or potassium hydroxide) and triglycerides from C16 carbon chain fatty acids through a saponification reaction or also called a lathering reaction at a temperature of 80 -100 o C. In this process, the fatty acids will be hydrolyzed by alkalis to form glycerin and raw soap. The application of science and technology from community service is to equip the younger generation in producing liquid dish soap for the students in Health Faculty Aufa Royhan University Padangsidimpuan and to attract students to be skilled and creative entrepreneurs. Activities carried out in the form of training with instructors from S-2 lecturers of the Pharmacy Study Program, Health Faculty Aufa Royhan University Padangsidimpuan include training in making dishwashing liquid soap as a creative and competitive entrepreneurial product. The results that have been achieved from this training activity in general are that students are very enthusiastic about participating in this training and they are able to make their own liquid dish soap for their own needs and market the dish soap as a source of income so that they can improve the entrepreneurial skills in Health Faculty Aufa Royhan University Padangsidimpuan